2015
DOI: 10.1007/s00795-015-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell in vitro labeling by hybrid fluorescent magnetic polymeric particles for application in cell tracking

Abstract: Mesenchymal stem cells (MSCs) are a type of adult stem cell that contains multi-differentiation and proliferative properties and that shows high treatment implications for many clinical problems. The outcome of stem cell transplantation is still limited due to many factors, especially their survival and their interaction with the microenvironment after transplantation. Molecular imaging is a challenging technique that has been used to overcome this limitation and is based on the concept of labeling cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…A central question for MSC-based therapies is: where do cells go after their transplantation? One of the limiting factors of MSC transplantation is their interaction with the microenvironment ( 109 ). Therefore, it is essential to provide information about stem cells homing, motility, migration, and allocation ( 110 ).…”
Section: Msc Tracking and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…A central question for MSC-based therapies is: where do cells go after their transplantation? One of the limiting factors of MSC transplantation is their interaction with the microenvironment ( 109 ). Therefore, it is essential to provide information about stem cells homing, motility, migration, and allocation ( 110 ).…”
Section: Msc Tracking and Imagingmentioning
confidence: 99%
“…- Magnetic polymeric nanoparticles to label MSC, for visualizing them by fluorescence microscopy ( 109 ).…”
Section: Msc Tracking and Imagingmentioning
confidence: 99%
“…In addition, the effectiveness of BMSC transplantation for tumor intervention can be observed in real time because of the progress in modern molecular imaging. [ 7 8 ] Molecular imaging probes, owing to their molecular structures, can bind to specific targets within living cells and thus facilitate the detection of the structures and properties of the targets and generation of signals that can be monitored in real time in situ and in vivo . [ 9 ] However, real-time monitoring of biological behaviors of the tumor in vivo , such as tumor proliferation and metastatic behaviors, before and after BMSC intervention, remains difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these results indicated that FITC@NPs coated with silica or CMCh are a valuable tool to investigate the interactions of NPs both in in vitro cell culture and in vivo. [238] Following studies aimed to label rMSCs using magnetic FITC@ChNPs, generated by Kaewsaneha et al [239,240] After incubation of rMSC with NPs, the labeling efficiency was timedependent, achieving the highest fluorescence after 24 h incubation with no impacts on cell viability. Labeled cells were then 3D imaged to check the location of NPs which were mainly detected in the cytoplasm, suggesting endocytosis as the uptake mechanism.…”
Section: Cellular Labelingmentioning
confidence: 99%
“…These results classify magnetic FITC@ChNPs as a powerful potential tool for rMSC labeling, allowing cell tracking and visualization by fluorimetry. [239] Kaewsaneha et al [241] used a method developed by Kaewsaneha et al, [240] incorporating iron oxide into polystyrene/ divinyl benzene/acrylic acid by miniemulsion polymerization while FITC was immobilized using chitosan as a spacer. The MW of chitosan employed in this method was high enough (300 kDa) to avoid direct contact between the iron core and FITC, so that quenching was prevented.…”
Section: Cellular Labelingmentioning
confidence: 99%